2021
DOI: 10.12982/vis.2021.041
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial resistance characteristics of Extended Spectrum Beta Lactamase (ESBL)- producing Escherichia coli from dairy farms in the Sleman district of Yogyakarta province, Indonesia

Abstract: Extended Spectrum Beta Lactamase (ESBL)-producing Escherichia coli (E. coli) infections are a global health challenge resulting from human contact with infected animals and contaminated farm environments. This study aims to identify antimicrobial resistance patterns of ESBL-producing E. coli isolated from dairy farms in the Sleman District of Yogyakarta Province, Indonesia. Ninety-three dairy farms with a history of antibiotic use in the previous 6 months were identified. Samples were collected from 6 differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 20 publications
0
13
0
1
Order By: Relevance
“…Sudarwanto et al (2017) found that out of 129 samples with resistance pattern to penicillin, tetracycline, streptomycin and trimethoprim, only 4 (3.1%) were ESBL E. coli. Another study by Maulana et al (2021) on the incidence of ESBL E. coli from several samples of dairy farms in the province of Yogyakarta reported that 50 (54%) were ESBL E coli, dominated by a pattern of resistance to trimethoprim, tretracycline and gentamicin. However, the pattern of resistance to aztreonam found in ESBL E. coli isolates (AS 27) in this study is a new finding that needs attention, considering that aztreonam is rarely used in the treatment of dairy cows in Indonesia.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sudarwanto et al (2017) found that out of 129 samples with resistance pattern to penicillin, tetracycline, streptomycin and trimethoprim, only 4 (3.1%) were ESBL E. coli. Another study by Maulana et al (2021) on the incidence of ESBL E. coli from several samples of dairy farms in the province of Yogyakarta reported that 50 (54%) were ESBL E coli, dominated by a pattern of resistance to trimethoprim, tretracycline and gentamicin. However, the pattern of resistance to aztreonam found in ESBL E. coli isolates (AS 27) in this study is a new finding that needs attention, considering that aztreonam is rarely used in the treatment of dairy cows in Indonesia.…”
Section: Discussionmentioning
confidence: 99%
“…In Indonesia, the first occurrence of ESBL E. coli was found in a milk sample from a dairy farm in West Java (Sudarwanto et al 2017). Reported on several samples from dairy farms in Yogyakarta province in 2021 (Maulana et al 2021), from dairy farm feces in East Java in 2019 (Putra et al 2019), from raw milk samples in 2021 (Ansharieta et al 2021), and milk samples from dairy cows in East Java in 2022 (Widodo et al 2022), its was found that E. coli from the samples contained ESBL encoding gene.…”
Section: Introductionmentioning
confidence: 99%
“…Nilai ini lebih rendah dari penelitian yang dilakukan oleh Schmid et al, (2013) dan Weber et al, (2021), dimana terdapat 32.8% dan 63.5% sampel dari peternakan sapi yang mengalami kejadian E. coli penghasil ESBL. Penelitian ini juga menunjukkan hasil yang lebih rendah dari penelitian yang dilakukan oleh Maulana et al (2021), dimana terdapat 25% sampel swab rektum sapi di Kabupaten Sleman, Yogyakarta mengalami kejadian ESBL.…”
Section: Hasil Dan Pembahasanunclassified
“…Multidrug resistance of Escherichia coli in rinse water from workers' hands demonstrates the risk of crosscontamination between dairy cattle and workers (Dahms et al 2015). However, the presence of the bacteria does not automatically demonstrate zoonotic transfer between dairy cattle and workers, as environmental contamination, such as by wastewater, may represent an even greater risk (Maulana et al 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Wastewater is the primary repository for antibiotics and bacteria resistant to antibiotics in the environment, and the environment is where microorganisms with the highest level of resistance to antibiotics are found (Maulana et al 2021). Therefore, E. coli in the environment of dairy farms indicates the potential for disease transmission from the dairy farm environment to the outside environment.…”
Section: Introductionmentioning
confidence: 99%